Effects of Smoking Habits on Omega-3 Food Intake in Adults - Lorensia, Amelia; Aditama, I Gede Agus Sindhu; Suryadinata, Rivan Virlando; Raharjo, Dian Natasya (Indonesian Journal of Human Nutrition, 2023)
Smoking habits have been shown to impact omega-3 food intake, and cigarette smoke can increase lipid peroxidation through the induction of oxidative stress.  Omega-3, an essential fatty acid, can be obtained through the consumption of fish, milk, eggs, and supplements. This cross-sectional research aimed to assess the relationship between omega-3 food intake and smoking habits. The research was conducted from March to June 2022 in Rungkut District, Surabaya, Indonesia. Data collected included the respondents’ quantities and frequency of consuming foods containing omega-3, namely fish, milk, and eggs. Additionally, the level of nicotine dependence among smokers was evaluated using the Fagerstrom Test for Nicotine Dependence (FTND). The method for data analysis was the chi-square test. The total respondents in this study were 116 people, consisting of 41 smokers and 75 non-smokers. No significant differences were observed in the consumption patterns of omega-3-rich foods, including eggs, fish, and milk, between smokers and non-smokers (p > 0.01 for each food item). However, a significant difference was observed in the consumption of supplements containing omega-3 between the smoker and non-smoker groups (p < 0.005). However, the overall omega-3 intake did not exhibit a significant difference between smokers and non-smokers. Notably, a higher proportion of respondents who smoked reported consuming omega-3 supplements compared to the non-smoker group. Consequently, there is a need to conduct further research to identify the underlying factors that influence the habit of smokers toward consuming omega-3.